Evaluasi Media Pembelajaran Materi Fikih Madrasah Aliyah - Mahfida Inayati; Mulyadi Mulyadi (Medan Resource Center, 2023)
Evaluation plays a vital role in learning as a deliberate and purposeful activity. Teachers consciously engage in learning evaluation to ascertain students' learning outcomes and receive feedback regarding their teaching practices. Evaluation directly relates to the purpose of an activity, measuring the extent to which a goal is achieved. Generally, evaluation is understood as a systematic process of determining the value of something—be it provisions, activities, decisions, work points, processes, individuals, objects, or others—based on specific criteria. It involves assessing and comparing the subject with predetermined criteria to gauge its performance against general standards and measure the effectiveness of the evaluation subject. Evaluation serves as an essential tool in assessing progress, identifying areas for improvement, and making informed decisions to enhance the learning process.